Length–weight relationships of six fish species from a nearshore artificial reef zone, northern Yellow Sea, China. (21st October 2021) - Song, Minpeng; Zhu, Lixin; Wang, Lu; Wang, Jinxiao; Nie, Zhaoyi; Zhang, Jiating; Jiang, Zhaoyang; Liang, Zhenlin
Abstract: This present study estimated the length–weight relationships of six fish species collected from the Xiaoshidao artificial reef zone, northern Yellow Sea. The samples were captured monthly from September 2020 to May 2021. During each sampling period, fish trap net (7 m, 20 mm mesh), consisting of 23 individual rectangular steel frames (22 × 35 cm) and one smaller‐sized steel frame (19 × 30 cm) at each end which was deployed at random locations in the artificial reef zone for 24 h. The precision of measurement for the fish specimens is 0.1 cm total length and 0.01 g wet weight. Four new maximum lengths were recorded for S. hubbsi (20.5 cm), S. ommaturus (50.1 cm), Z. elongatus (43.5 cm) and P. fangi (20.0 cm).